The experience of a multidisciplinary team in welcoming vulnerable migrants in a rural Italian reception centre: a study using multidimensional textual analysis - Mariachiara Figura; Gianluca Pucciarelli; Silvio Simeone; Paola Arcadi; Bartosz Uchmanowicz; Ercole Vellone; Rosaria Alvaro (BMC Nursing)
Abstract Background In recent years, migration it has significantly increased due to political conflicts, economic instability, and environmental crisis. In migrant reception centers, interdisciplinary collaboration is essential. However, professionals face complex challenges, such as systemic barriers, fragmented services, bureaucratic inefficiencies, and a lack of culturally competent training, particularly in rural contexts where resources are limited. Understanding how professionals navigate the complexities of their roles is crucial. The aim of this study is to explore the experiences of a multidisciplinary team involved in the reception of vulnerable migrants in a rural Italian reception center. Methods A qualitative study with semi-structured interviews was conducted in April 2022 with professionals working in an Italian reception center. The interview questions focused on professionals’ experiences, the strengths and challenges of their work, potential improvements to the reception process, the needs and requests reported by migrants, and the priority areas to address, recommended interventions. The data were analyzed using Automatic Analysis of Textual Data, allowing for the identification of latent dimensions and thematic clusters. Correspondence analysis basing on professionals working area, Hierarchical Discending Classification and Principal Component Analysis were conducted. The research report adhered to the Consolidated Criteria for Reporting Qualitative Research (COREQ) guidelines. Results The sample consisted of sixteen professionals, divided into three working areas: healthcare, social and organizational. Thematic clusters revealed distinct focuses: socioeducational support emphasized relational and emotional care, healthcare professionals addressed cultural barriers and clinical complexities, and organizational roles concentrated on systemic frameworks and sustainability. Two principal dimensions of care emerged: the cultural dimension of care, which integrates clinical, cultural, and symbolic aspects, and personalized systemic integration planning, highlighting the balance between immediate needs and long-term systemic strategies. Conclusion The findings underscored the critical importance of interdisciplinary collaboration and culturally sensitive approaches in migrant care. Relational dynamics must be harmonized with systemic planning to address the diverse and evolving needs of beneficiaries. The study also highlights unique challenges in rural contexts, including resource limitations and geographic isolation, which require innovative and context-specific solutions. This study provides context-specific insights that may inform integrated care strategies in similar rural or resource-limited migrant settings. By emphasizing the interplay of cultural, clinical, and systemic dimensions, it offers a framework for improving health outcomes and fostering sustainable integration in both rural and global contexts. Future studies should explore these dynamics across diverse settings to further inform clinical practice, research, and policy development. Clinical trial number Not applicable.